High Efficiency Inorganic Perovskite Solar Cells Based On Low Trap Density and High Carrier Mobility CsPbI3 Films. (12th September 2022) - Yuan, Jifeng; Zhang, Di; Deng, Binbin; Du, Jiuyao; Choy, Wallace C. H.; Tian, Jianjun
Abstract: Inorganic perovskite CsPbI3 has exhibited promising performance in single‐junction solar cells, but the grain boundaries (GBs) in its film cause the formation of the defects with deep energy levels (such as iodide vacancy ( V I )) and impede the transport of carriers, worsening the efficiency and stability of the solar cells. Here, a CsPbI3 precursor is devised with thiophenol series ligands (TP‐ligands) containing both SH and π‐conjugated molecules. The strong interaction between the SH group (Lewis base) and PbI2 (Lewis acid) suppresses the formation of PbI4 2− in perovskite solution, thus suppressing the formation of V I in the film accordingly. The terminal groups, such as ‐F and ‐NH2, are employed to achieve an appropriate evaporation speed of the ligands and prevent the oxidation of the thiophenol group, then a high‐quality perovskite film with low trap density is obtained. In addition, the functional group π‐conjugated molecules provide additional carrier transmission channels at the GBs to increase carrier mobility, which facilitates the exciton separation and prolongs the charge lifetime. The CsPbI3 solar cell shows a considerable power conversion efficiency of 20.1% with an open‐current voltage of 1.18 V and a high fill factor of 83.5% and excellent working stability. Abstract : Thiophenol ligands are introduced into the CsPbI3 precursor, resulting in a high‐quality perovskite film with low trap density and high carrier mobility, which facilitates the exciton separation and prolongs the charge lifetime, thus achieving a considerable power conversion efficiency of 20.1% for the all‐inorganic perovskite solar cells.